Organizing and Implementing Export Pricing: Performance Effects and Moderating Factors. Issue 1 (March 2019) - Hofer, Katharina Maria; Niehoff-Hoeckner, Lisa Maria; Totzek, Dirk
Relatively little is known about pricing in the export business, particularly how to organize and implement export pricing within firms and how these issues affect export performance. Therefore, this study investigates antecedents of export performance, specifically the organizational aspects of export pricing and price adaptation and the moderating role of export market characteristics, including export market turbulence, enforcement of contracts, and corruption ranks of the export market. Using a large-scale survey sample of 295 exporting firms in Austria and Germany and secondary data on the export markets involved, the authors show that both the intensity of internal pricing coordination and price adaptation have a positive effect on export performance. Specifically, in highly turbulent export markets, the intensity of internal pricing coordination contributes to export performance. Furthermore, a high level of horizontal dispersion of pricing authority is advisable in countries in which the enforcement of contracts is difficult.